PENINGKATAN KETERLIBATAN MAHASISWA DALAM PEMBELAJARAN BIOSTATISTIK DENGAN METODE KOOPERATIF MELALUI MEDIA LEMBAR KERJA MAHASISWA (LKM) DI PROGRAM STUDI PERUMAHSAKITAN - Nia Murniati; Supriadi Supriadi; Tri Gunadi (Jurnal Vokasi Indonesia, 2013)
ABSTRACT -This research is motivated by the lack of passionate students of the Program StudiPerumahsakitan Vokasi in the following study courses Biostatistics, because the teaching method does not makethe students become active and participate. Consequently Biostatistics courses often leave some students areforced to repeat the due credit limit does not reach the threshold value eventually pass (C) and of course is verydetrimental to the student having to repeat the course credit until they intern (last semester). This study is aclass act with the entire student subjects RS1 50 people Academic Year 2012/2013 in the University ofIndonesia with the material limits of Biostatistics emphasis on material probability. Results were obtained incycle 1 achieved an average score of 3770/5000 = 75.4, cycle 2 average scores achieved 4105/5000 = 82.1and cycle 3 achieved an average score of 4585/5000 = 91.7. Conclusion The method of cooperative learningapproach through the media LKM have a positive impact in improving student achievement is marked by anincrease in the average scores achieved in each cycle, and through the media worksheet can increase studentinterest and motivation shown by increased activity in the classroom discussion. Advice is to carry out acooperative approach through the media LKM method requires the preparation of a fairly mature, so thelecturer must be able to determine the learning scenario can actually be applied in order to obtain optimalresults.Peningkatan Keterlibatan Mahasiswa dalam Pembelajaran Biostatistik dengan Metode Kooperatif Melalui MediaLembar Kerja Mahasiswa (LKM) di Program Studi PerumahsakitanNia M, Supriadi, Tri GVolume 1, Nomor 2, pp 84-9685Keywords: class action research, cooperative learning, worksheet students.